Medium Promoting Sporulation of Bacillus larvae and Metabolism of Medium Components - Dingman, D. W. (1983)
A new medium, designated TMYGP broth, was developed that allowed the honeybee pathogen Bacillus larvae NRRL B-3650 to produce up to 5 × 10(8) spores per ml of culture (microscopic count). This species normally sporulates poorly, if at all, in artificial broth media. An aeration rate lower than that normally used to cultivate other Bacillus species was required for sporulation. During the exponential growth phase, acids were produced by catabolism of yeast extract components, causing a decrease in pH of the medium. Thereafter, the pH began to increase, probably because of derepression of the citric acid cycle and consumption of the acids. Only after this time did usage of glucose from the medium occur. Thus, glucose usage seems to be regulated by catabolite repression. The presence of glucose was needed for one or more of the later events of sporulation. Of many substances tested, only gluconic acid and glucosamine partially substituted for glucose as a requirement for sporulation. Pyruvate was also required for good sporulation. It was metabolized during the late-exponential phase of growth.